THBD sequence variants potentially related to recurrent pregnancy loss (2017)
Recurrent pregnancy loss (RPL) is a frequently occurring disease, which is classified as idiopathic in more than 50% of cases. THBD, the endothelial cell receptor for thrombin, has been associated with distinct biological processes and considered a coherent RPL-related candidate gene. In the present study, we have sequenced the complete coding region of THBD in 262 patients affected by RPL. Bioinformatics analysis and screening of controls strongly suggested that the THBD-p.Trp153Gly mutation might be related to RPL aetiology. It could be used, after its validation by functional assays, as a molecular marker for diagnostic/prognostic purposes. © 2017 The Author(s).